Influence of different types of compression garments on exercise-induced muscle damage markers after a soccer match - Marqués-Jiménez, D.; Calleja-Gonzalez, J.; Arratibel-Imaz, I.; Delextrat, A.; Uriarte, F.; Terrados, N. (Research in Sports Medicine, 2018)
There is not enough evidence of positive effects of compression therapy on the recovery of soccer players after matches. Therefore, the objective was to evaluate the influence of different types of compression garments in reducing exercise-induced muscle damage (EIMD) during recovery after a friendly soccer match. Eighteen semi-professional soccer players (24 ± 4.07 years, 177 ± 5 cm; 71.8 ± 6.28 kg and 22.73 ± 1.81 BMI) participated in this study. A two-stage crossover design was chosen. Participants acted as controls in one match and were assigned to an experimental group (compression stockings group, full-leg compression group, shorts group) in the other match. Participants in experimental groups played the match wearing the assigned compression garments, which were also worn in the 3 days post-match, for 7 h each day. Results showed a positive, but not significant, effect of compression garments on attenuating EIMD biomarkers response, and inflammatory and perceptual responses suggest that compression may improve physiological and psychological recovery.